The Influence of Financial Management on Organizational Performance - Luther Hasan Lase; Ristianto (AKADEMI TEKNIK ADI KARYA, 2026)
Effective financial management plays a strategic role in improving organizational performance by ensuring the efficient allocation of resources, strengthening financial accountability, and supporting informed managerial decision-making. This study aims to examine the influence of financial management on organizational performance. A quantitative explanatory research design was employed using a survey approach. Data were collected from managers, financial officers, and administrative staff across various organizations through structured questionnaires distributed using proportional random sampling. The measurement instruments were tested for validity and reliability prior to hypothesis testing. The collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both the measurement model and the structural relationships between financial management and organizational performance.The findings reveal that financial management has a positive and statistically significant effect on organizational performance. Effective financial planning, budgeting, financial reporting, cash flow management, and internal financial control contribute substantially to enhancing organizational efficiency, operational effectiveness, accountability, and the achievement of strategic objectives. The structural model demonstrates strong explanatory power, indicating that improvements in financial management practices significantly increase organizational performance. These findings support the Resource-Based View (RBV), which emphasizes that sound financial management represents a valuable organizational capability capable of generating sustainable competitive advantages. The study concludes that organizations should strengthen financial governance through transparent budgeting systems, accurate financial reporting, digital financial management technologies, and continuous capacity development for financial personnel. Such initiatives are expected to improve organizational sustainability, accountability, and overall institutional performance.